The role of neuraminidase 1 (NEU1) in cytokine release by primary mouse mesangial cells and disease outcomes in murine lupus nephritis - Jessalyn Rodgers; Kamala Sundararaj; Evelyn Bruner; Bethany Wolf; Tamara K. Nowling (Taylor & Francis Group, 2021)
The importance of altered glycosphingolipid (GSL) metabolism is increasingly gaining attention as a characteristic of multiple chronic kidney diseases. Previously, we reported elevated levels of GSLs and neuraminidase (NEU) enzyme activity/expression in the urine or kidney of lupus patients and lupus-prone mice, and demonstrated NEU activity mediates the production of cytokines by lupus-prone mouse primary mesangial cells. This mediation occurs in part through TLR4 and p38/ERK MAPK signalling in response to lipopolysaccharide (LPS) and lupus serum (LS). However, the precise role of NEU1, the most abundant NEU in the kidney, is incompletely known. In this study, we investigated the effect of genetically reduced Neu1 levels in vitro and in vivo. Mesangial cells from non-autoimmune prone Neu1+/− C57BL/6 mice had significantly reduced NEU activity, cytokine expression and cytokine secretion in response to LS and LPS, thereby suggesting reducing Neu1 expression may reduce the inflammatory response in lupus nephritis. Disease was assessed in female B6.SLE1/2/3 lupus-prone mice with genetically reduced levels (Neu1+/−) or wild-type levels (Neu1+/+) of Neu1 from 28 to 44 weeks of age along with aged-matched C57BL/6 controls. Renal disease was unexpectedly mild in all B6.SLE1/2/3 mice despite evidence of systemic disease. B6.SLE1/2/3 Neu1+/− mice exhibited significantly reduced levels of renal NEU1 expression and changes in renal α-2,6 linked sialylated N-glycans compared to the Neu1+/+ or healthy C57BL/6 mice, but measures of renal and systemic disease were similar between the B6.SLE1/2/3 Neu1+/+ and Neu1+/− mice. We conclude that NEU1 is the NEU largely responsible for mediating cytokine release by mesangial cells, at least in vitro, but may not be involved in modulating renal GSL levels in vivo or impact onset of nephritis in lupus-prone mice. However, the effect of reduced NEU1 levels on disease may not be appreciated in the mild disease expression in our colony of B6.SLE1/2/3 mice. The impact of the altered renal sialylated N-glycan levels and potential role of NEU1 with respect to established nephritis (late disease) in lupus-prone mice bears further investigation.